2015
DOI: 10.1136/archdischild-2014-306129
|View full text |Cite
|
Sign up to set email alerts
|

Serial cranial ultrasonography or early MRI for detecting preterm brain injury?

Abstract: Advanced serial CUS seems highly effective in diagnosing preterm brain injury, but may miss cerebellar abnormalities. Although MRI does identify these lesions, feasibility is limited. Improved safety, better availability and tailored procedures are essential for MRI to increase its value in clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 29 publications
1
44
1
6
Order By: Relevance
“…When predicting outcomes with the signals on T2-quantification MR imaging, infants' ages should be considered cautiously. Although not a very early neuroimaging indicator compared with other studies using term-equivalent age MR imaging, 3 our T2-quantification model could still enhance the clinical judgment in high-risk preterm infants because the diagnosis of cerebral palsy might sometimes be equivocal before 18 months of age.…”
Section: 23mentioning
confidence: 92%
See 2 more Smart Citations
“…When predicting outcomes with the signals on T2-quantification MR imaging, infants' ages should be considered cautiously. Although not a very early neuroimaging indicator compared with other studies using term-equivalent age MR imaging, 3 our T2-quantification model could still enhance the clinical judgment in high-risk preterm infants because the diagnosis of cerebral palsy might sometimes be equivocal before 18 months of age.…”
Section: 23mentioning
confidence: 92%
“…2 MR imaging is considered a good tool for early diagnosis of brain injury in prematurity, but the conventional qualitative approach remains subjective. 3,4 The incidence of macroscopic cystic-necrotic periventricular leukomalacia has markedly declined, and new forms of microscopic focal or diffuse nondestructive white matter injury are emerging. 5 However, this microscopic necrosis and gliosis is not readily detected by conventional MR imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent multicenter epidemiological studies reported an incidence rate of IVH of 25-30% for very low birth weight infants and even higher for extreme low birth weight infant [4,5]. The described rate for low-grade IVH (grades I-II) is 11% and for severe IVH (grades III-IV) is 3-5% [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cranial ultrasonography (US) is the most commonly used imaging technique to diagnose IVH, because of its high sensitivity for detecting acute bleeding, its portability, and the lack of ionizing radiation [7].…”
Section: Introductionmentioning
confidence: 99%